Do Parents Have “The Talk” or Believe They Should?: Parent–Child Conversations About Interacting with the Police - Wylie, Breanne E. (Journal of developmental and life-course criminology, 2024)
Parent–child conversations about how to interact with the police are colloquially known as “The Talk.” Studies have largely focused on the influence of age, race, and gender on the occurrence of such conversations. We extended this examination to other potentially influential factors as well as beliefs about whether parents should have “The Talk.” Parents of 5 to 17 year olds (N = 1131) completed questionnaires to assess the influence of demographics, child factors, and parent factors, on whether parents have talked to their child about how to interact with the police, and whether they believe parents should have such conversations. Though most parents believed parents should have “The Talk,” only half of parents had “The Talk” (around age 7). Binary logistic regressions revealed that whereas parental factors (anxiety, perceived discrimination) reduced beliefs that parents should have such conversations, child factors (affective reactivity) influenced whether parents had “The Talk.” Also, with greater perceived police bias and legitimacy, parents were more likely to have “The Talk” and believed parents should. Given that not all parents are having “The Talk” or believe parents should, we conclude that parents might need help in learning how to talk to their children about how to interact with the police.